Social control agents and the evolving definition of wrongdoing: the case of the gray area around the Mafia - Cappellaro, G; Compagni, A; Vaara, E (Emerald Publishing, 2023)
In this paper, we investigate the process by which social control agents define wrongdoing over time and the principles they employ in drawing the boundary between right and wrong. We empirically examine how Italian state actors sought over four decades to categorize behaviors in the so-called “gray area,” i.e. the conduct of individuals supportive of the mafia organization Cosa Nostra and its criminal aims, but not members of the organization. Based on an archival analysis of texts produced since the 1960s we reconstruct how state actors started from a preliminary definition of wrongdoing, moved to stigmatize the behaviors in question on moral grounds, and ultimately criminalized them with legal sanctions. We conceptualize the main principles behind this evolving categorization as intentionality of conduct, freedom of choice, and scope of harm. The paper contributes to the debate on the factors and conditions shaping the definition of wrongdoing over time and the contribution that social control agents provide to this aim.